Performance of Forward Osmosis Using Various Membranes - Qasim, Muhammad (2013)
A Master of Science thesis in Chemical Engineering by Muhammad Qasim entitled, "Performance of Forward Osmosis Using Various Membranes," submitted in January 2013. Thesis advisor is Dr. Raafat Alnaizy and Co-Advisor Dr. Ahmad Aidan. Available are both soft and hard copies of the thesis.